Photocatalytic organic pollutants degradation in metal-organic frameworks - Wang, Chong-Chen; Li, Jian-Rong; Lv, Xiu-Liang; Zhang, Yan-Qiu; Guo, Guangsheng (Energy & environmental science, 2014)
Efficient removal of organic pollutants from wastewater has become a hot research topic due to its ecological and environmental importance. Traditional water treatment methods such as adsorption, coagulation, and membrane separation suffer from high operating costs, and even generate secondary pollutants. Photocatalysis on semiconductor catalysts (TiO 2 , ZnO, Fe 2 O 3 , CdS, GaP, and ZnS) has demonstrated efficiency in degrading a wide range of organic pollutants into biodegradable or less toxic organic compounds, as well as inorganic CO 2 , H 2 O, NO 3 − , PO 4 3− , and halide ions. However, the difficult post-separation, easy agglomeration, and low solar energy conversion efficiency of these inorganic catalysts limit their large scale applications. Exploitation of new catalysts has been attracting great attention in the related research communities. In the past two decades, a class of newly-developed inorganic-organic hybrid porous materials, namely metal-organic frameworks (MOFs) has generated rapid development due to their versatile applications such as in catalysis and separation. Recent research has showed that these materials, acting as catalysts, are quite effective in the photocatalytic degradation of organic pollutants. This review highlights research progress in the application of MOFs in this area. The reported examples are collected and analyzed; and the reaction mechanism, the influence of various factors on the catalytic performance, the involved challenges, and the prospect are discussed and estimated. It is clear that MOFs have a bright future in photocatalysis for pollutant degradation. This review summarizes research advances in photocatalytic organic pollutant degradation in metal-organic frameworks.